Apresente uma derivação à extrema direita (DED) da sentença a = a * (b - c) + (d / e) sobre a gramática a seguir.
G = ({A, B, C, D, E, F, G}, {a, b, c, d, e, =, +, -, *, /, (, )}, P, A)
P = {< A > -> < G > = < B >
< B > -> < D > < C > | < D >
< C > -> + < D > < C > | - < D > < C > | + < D > | - < D >
< D > -> < F > < E > | < F >
< E > -> * < F > < E > | / < F > < E > | * < F > | / < F >
< F > -> ( < B > ) | < G >
< G > -> a | b | c | d | e }
< A >
< G > = < B >
< G > = < D > < C >
< G > = < D > + < D >
< G > = < D > + < F >
< G > = < D > + ( < B > )
< G > = < D > + ( < D > )
< G > = < D > + ( < F > < E > )
< G > = < D > + ( < F > / < F > )
< G > = < D > + ( < F > / < G > )
< G > = < D > + ( < F > / e )
< G > = < D > + ( < G > / e )
< G > = < D > + ( d / e )
< G > = < F > < E > + ( d / e )
< G > = < F > * < F > + ( d / e )
< G > = < F > * ( < B > ) + ( d / e )
< G > = < F > * ( < D > < C > ) + ( d / e )
< G > = < F > * ( < D > - < D > ) + ( d / e )
< G > = < F > * ( < D > - < F > ) + ( d / e )
< G > = < F > * ( < D > - < G > ) + ( d / e )
< G > = < F > * ( < D > - c ) + ( d / e )
< G > = < F > * ( < F > - c ) + ( d / e )
< G > = < F > * ( < G > - c ) + ( d / e )
< G > = < F > * ( b - c ) + ( d / e )
< G > = < G > * ( b - c ) + ( d / e )
< G > = a * ( b - c ) + ( d / e )
a = a * ( b - c ) + ( d / e )